Efficacy of Some Botanicals in Controlling Brinjal Shoot and Fruit Borer, Leucinodes orbonalis (Progressive Agriculture, 2013)
Efficacy of some botanicals viz., neem oil, karanja oil and mahogoni oil at different concentrations was determined against brinjal shoot and fruit borer (BSFB). Three botanical oils were evaluated by assessing larval mortality in laboratory. Neem oil at 4% concentration showed lowest larval survivability (26.67%) while mahogoni oil caused highest survivability (68.89%) at 2% concentration. The effect of botanical oils on larval survivability decreased proportionally with the increase of concentrations. Considering the efficacy of all concentrations the order of toxicity was neem oil>karanja oil>mahogoni oil. The effectiveness of the botanicals viz., neem oil (4%), karanja oil (4%), mahogoni oil (4%), neem cake (250 kg/ha), neem oil + neem cake (4% + 250 kg/ha) were evaluated by application at 15 days interval against BSFB in the field. The highest percentage of reduction (70.44% infested shoots/plant) of BSFB was found in neem oil + neem cake. Minimum reduction of shoot infestation by BSFB was observed in neem cake treated plot. Similiar efficacy was found in case of reduction percentage of fruit infestation by BSFB.DOI: http://dx.doi.org/10.3329/pa.v20i1-2.16847 Progress. Agric. 20(1 & 2): 35 42, 2009